2006
DOI: 10.1002/jcp.20862
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase mediates preconditioning in cardiomyocytes by regulating activity and trafficking of sarcolemmal ATP‐sensitive K+ channels

Abstract: Brief periods of ischemia and reperfusion that precede sustained ischemia lead to a reduction in myocardial infarct size. This phenomenon, known as ischemic preconditioning, is mediated by signaling pathway(s) that is complex and yet to be fully defined. AMP-activated kinase (AMPK) is activated in cells under conditions associated with ATP depletion and increased AMP/ATP ratio. In the present study, we have taken advantage of a cardiac phenotype overexpressing a dominant negative form of the a2 subunit of AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 52 publications
7
107
2
2
Order By: Relevance
“…In particular, changes in sodium-and calcium-activated potassium channels or in Ca 2+ homeostasis, which have also been suggested to contribute to myotonia in DM1 (55)(56)(57)(58)(59)(60), may mediate some of the observed effect. Consistently, AMPK has been shown to modulate chloride and potassium channels in several cell types, including cardiomyocytes (61,62). Such mechanisms may also contribute to the beneficial effect of rapamycin, as it occurs in the absence of splicing changes.…”
Section: Discussionmentioning
confidence: 86%
“…In particular, changes in sodium-and calcium-activated potassium channels or in Ca 2+ homeostasis, which have also been suggested to contribute to myotonia in DM1 (55)(56)(57)(58)(59)(60), may mediate some of the observed effect. Consistently, AMPK has been shown to modulate chloride and potassium channels in several cell types, including cardiomyocytes (61,62). Such mechanisms may also contribute to the beneficial effect of rapamycin, as it occurs in the absence of splicing changes.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, AMPK is also activated during ischemic preconditioning (40,41), the physiologic phenomenon by which preceding short durations of ischemia decrease the susceptibility to necrosis during more prolonged and potentially injurious ischemia. AMPK is also activated by other treatment regimens that prevent ischemic injury, such as heat shock (10), adrenergic stimulation (42), and nitric oxide (43).…”
Section: Discussionmentioning
confidence: 99%
“…Culmsee and et al showed that the transient activation of AMPK with low concentrations of AICAR (0.1 mM) protected hippocampal neurons during glucose deprivation, metabolic, excitotoxic, and oxidative stress (Culmsee et al, 2001). As the induction of AMPK activity has been linked to the preconditioning of cells against energetic stress (Peralta et al, 2001;Sukhodub et al, 2007), Culmsee et al may have inadvertently preconditioned their neurons before stimulation by transiently increasing AMPK activity. In a separate study, McCullough et al (McCullough et al, 2005) identified that the prolonged exposure of neurons to AICAR and the continuous activation of AMPK increased neuronal injury during ischemia (see also Fig.…”
mentioning
confidence: 99%